2015
DOI: 10.1002/anie.201506500
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Transcription of Exogenous mRNA in Platelets Using Protocells

Abstract: Transcribing exogenous RNA in eukaryotic cells requires delivering DNA to their nuclei and changing their genome. Nuclear delivery is often inefficient, limiting the potential scope of gene therapy and synthetic biology. These challenges may be overcome by techniques that allow for extranucleate transcription within eukaryotic cells. Protocells have been developed that enable transcription inside of liposomes; however, it has not yet been demonstrated whether this technology can be extended for use within euka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In a cell-free synthesis system, it was demonstrated that such a construct could work functionally within liposomes (Ishikawa, Sato, Shima, Urabe, & Yomo, 2004). (Chan, Novakowski, Law, Klein-Bosgoed, & Kastrup, 2015).…”
Section: Liposomesmentioning
confidence: 99%
“…In a cell-free synthesis system, it was demonstrated that such a construct could work functionally within liposomes (Ishikawa, Sato, Shima, Urabe, & Yomo, 2004). (Chan, Novakowski, Law, Klein-Bosgoed, & Kastrup, 2015).…”
Section: Liposomesmentioning
confidence: 99%
“…The harnessing of biological and abiological systems that mimic some aspects of cellular life has gone from simple mimicry to attempts at developing technologies that influence the behavior of bacterial [17,18,54,59,120,121] and eukaryotic cells [17,[121][122][123]. Therefore, studies focused on chemical communication not only inform our understanding of biology but also help lay the groundwork for future therapies that exploit artificial cells that can interface with and control natural cells.…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…Washed platelets were loaded with liposomes as previously described, with minor modifications [16]. Briefly, 4.3 lM of human alpha thrombin or DFP active site blocked human alpha thrombin (Haematologic Technologies Inc. Essex Junction, VT, USA) in Tris-buffered saline (TBS) was added to a 5-mg lipid film, consisting of 1,2dioleoyl-sn-glycero-3-phosphocholine:cholesterol:1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPC:chol: DOPE; 23:23:4; Avanti Polar Lipids, Alabaster, AL, USA, cholesterol from Sigma, Oakville, Canada), and extruded five times through a 200-nm filter using a LIPEX extruder (Northern Lipids Inc., Burnaby, Canada).…”
Section: Preparing and Characterizing Liposomal Thrombinmentioning
confidence: 99%
“…Purified liposomes were added to isolated platelets (1:100 v/v) and incubated at room temperature for 1 h with gentle agitation, in order for uptake to occur. The uptake of liposomes into platelets was confirmed as previously described [16]. To remove excess liposomes, platelets and liposomes were centrifuged at 250 9 g for 5 min and the supernatant was removed.…”
Section: Loading Platelets With Liposomal Thrombinmentioning
confidence: 99%
See 1 more Smart Citation